Master training in Agribusiness and Rural Development at the University of Zagreb - László Kárpáti (Apstract: Applied Studies in Agribusiness and Commerce, 2007)
The title of the proposed JEP project is: “Agribusiness Higher EducAtion Development” with the acronym AHEAD. This curriculum development project – in case of acceptance – will last for three years, from July 2005 and June 2008. The primary project site is the University of Zagreb, Croatia; the contractor and the co-ordinator institution is the University of Debrecen, Hungary. In the consortium, 3 further European universities (University of Hohenheim, Wageningen University and Scottish Agricultural College) will participate, from the Croatian side the Ministry of Agriculture, Forestry and Water Management and an additional 7 Croatian institutes will also be involved. The total number of members in the consortium is 13. The main objective of the AHEAD project is to establish new BSc and MSc programmes in Croatia at two Faculties of the University of Zagreb. These are as follows: Agricultural and Rural Development, Food Safety and Quality Management and pilot MSc training in Agribusiness and Rural Development. These are preceded by faculty retraining programmes in food safety and quality management, as well as agribusiness and commerce within the framework of a MBA programme accredited by the International MBA Network. The professional content of the project is a modernised curriculum and training palette that would be available by the end of this project at the University of Zagreb, serving not only the higher education of the country, but the demand of the Croatian national economy as well, in line with the basic principles of the European Union.